1941
DOI: 10.1021/ja01847a053
|View full text |Cite
|
Sign up to set email alerts
|

Metalation and Halogen-Metal Interconversion Reactions of Some Halogenated Phenyl Ethers

Abstract: The extensive application of the halogen-metal interconversion reaction to aryl halides and the two-stage metalation of a number of halogenated aryl ethers [reactions (I) and (II)] have suggested a study of the effect of orientation, the kind of halogen and the nature of the RLi compound on the reactions of some halogenated phenyl ethers.Orientation.-The first illustrations of the halogen-metal interconversion reaction with bromoaryl ethersla,b,c involved bromine ortho to the ether linkage [reaction (IV)]. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…For the most part this has been due to concern that the –Br or –I substituent will preferentially undergo rapid X/Li exchange. Both Gilman and Wittig attempted ortho ‐lithiation of p ‐bromoanisole with both eventually realizing that the transformation illustrated in Equation (1) was occurring. Wittig went on to investigate the use of PhLi for the ortho ‐lithiation of the haloanisoles, ultimately isolating the anticipated triarylcarbinol derived from p ‐BrA and benzophenone in 70 % yield [Equation ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the most part this has been due to concern that the –Br or –I substituent will preferentially undergo rapid X/Li exchange. Both Gilman and Wittig attempted ortho ‐lithiation of p ‐bromoanisole with both eventually realizing that the transformation illustrated in Equation (1) was occurring. Wittig went on to investigate the use of PhLi for the ortho ‐lithiation of the haloanisoles, ultimately isolating the anticipated triarylcarbinol derived from p ‐BrA and benzophenone in 70 % yield [Equation ].…”
Section: Introductionmentioning
confidence: 99%
“…This was an achievement at the time in that for seventy years, there was a fear of the intervention of a rapid halogen/lithium exchange followed by a secondary ortho-lithiation [Equation (1)]. Both Henry Gilman [8] and George Wittig, [9] the co-discovers of the ortho-lithiation reaction, also elucidated the sequence shown below.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bromine–lithium exchange reaction is certainly one of the most fundamental synthetic transformations [ 39 ]. Although this reaction was reported by C. S. Marvel in 1927 [ 40 ], G. Wittig [ 41 ] and H. Gilman [ 42 44 ] were the first to apply it in organic synthesis in the late thirties. Since then, this reaction has been considered as a mature method lacking both appeal and surprise [ 33 ], and only new applications of this reaction or mechanistic studies have been reported [ 30 , 32 – 33 45 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…6 In the early reports of the metal/halogen exchange reaction methyllithium was described as the least effective of all the alkyllithiums investigated and it was therefore believed to have little synthetic utility in this reaction. 11,12 We have found that if methyllithium is reacted with aryl bromides bearing a suitable ortho substituent it is very effective in the metal/halogen exchange reaction (Scheme 1). 9,10 Included in the small number that are known are examples where the methyl bromide by-product reacted with the newly formed aryllithium to produce the corresponding methyl compound.…”
mentioning
confidence: 99%